Animal protein in the pot : the ethnozoology perspective of native Papuans - Freddy Pattiselanno (Journal of Tropical Ethnobiology, 2005)
Human collect great variety of food resources from wild animal, including mammals, birds, reptiles, amphibians, fish and also invertebrates. Wildlife resources are utilized in various ways among tribes that are reflects economic, sociocultural and ecological differences. Certain animal species are extremely popular to particular tribes therefore they are commonly hunted for certain reason such as food for protein source. The present paper reviewed and discussed food security based on wildlife utilization in Papua.